Exploring factors that influence positive WOM in the health insurance industry. Issue 2 (2nd April 2020) - Leon, Steven; Nakayama, Makoto
Abstract: Health insurance companies have an interest in understanding what factors may lead to positive word-of-mouth (WOM) from consumers. This research identifies factors that influence positive WOM about health insurance firms. Using data collected from 425 insurance policy holders, we find influential factors vary depending on the purchase source. Significant factors identified in the study that influence positive word-of-mouth include service quality, plan satisfaction, and plan type (individual vs. family). Further, claim count, preferred information source, and deductible levels also affect the spread of positive WOM differently among purchase sources. The study concludes with a discussion of implications and future research.